(untitled) (Al-Academy, 2019)
The research topic (The dramatic structure transformations in the Iraqi Feature Film) studies the dramatic structure and its transformations in the Iraqi feature film. The research determined the research problem and the need for it in addition to the aims and the limits of the study as well as its importance. The theoretical framework consists of the following themes: the dramatic transformations mechanism and dramatic data in the Iraq film 1957-2003 then the dramatic values transformations and the performance contradictions in the Iraqi film.The research, after concluding the theoretical framework, came up with a number of indicators of the theoretical framework that have been used as a tool to analyze the sample. The research procedures included analyzing the study sample (Baghdad is a Pink Dream, script and direction by Faisal Al-Yaasiri), the results of the analysis and the conclusions followed by a list of references and margins